Penerapan Media Pembelajaran Berbasis Quizizz dalam Meningkatkan Hasil Belajar pada Pembelajaran IPAS Kelas V MI Nurul Hidayah Kabupaten Bogor - Ardiansyah, Fahmi; Asmahasanah, Salati; Rivani, Falizar (Lembaga Yasin AlSys, 2025)
The limited number of studies on the use of interactive technology-based learning media—particularly Quizizz—in Ilmu Pengetahuan Alam dan Sosial (IPAS) instruction at madrasah ibtidaiyah forms the background of this research, considering the low learning outcomes and limited student participation in conventional learning, which impact the effectiveness of the teaching and learning process. This study aims to analyze the effectiveness of using Quizizz in improving student learning outcomes and engagement in Grade V IPAS at MI Nurul Hidayah, Bogor Regency. The method employed is Classroom Action Research (CAR) conducted over two cycles, encompassing the stages of planning, action implementation, observation, and reflection, with 25 purposively selected students as research subjects. Data were collected through observations of teacher and student activities, as well as learning outcome tests in each cycle, and analyzed using descriptive quantitative and qualitative methods. The results showed an increase in the average learning outcomes from 49% in the pre-cycle to 76% in Cycle I and 81% in Cycle II. Classical mastery learning improved from 20% in the pre-cycle to 64% and 72% in each subsequent cycle. Teacher activity increased from 83% to 87%, and student participation from 81% to 87%. These findings align with constructivist theory and the gamification approach, which emphasize active engagement and enjoyable learning experiences in improving academic performance. Quizizz proved to offer an interactive experience through digital quizzes and instant feedback, enhancing student motivation, focus, and retention of IPAS content. The main conclusion of this study is that Quizizz-based learning media is effective in improving both learning outcomes and student participation. Theoretically, this research enriches the literature on digital technology integration in 21st-century education, while practically, it provides recommendations for teachers to utilize interactive media to create engaging, meaningful, and student-responsive learning environments. This study also opens pathways for future research comparing the effectiveness of various digital learning platforms on student motivation and long-term retention.